Essex-Lopresti injuries: an update. - Masouros, Panagiotis T; Apergis, Emmanuel P; Babis, George C; Pernientakis, Stylianos S; Igoumenou, Vasilios G; Mavrogenis, Andreas F; Nikolaou, Vasileios S (EFORT Open Rev, 2019)
Reconstruction of the central band of the interosseous membrane is an emerging procedure implemented in the treatment of longitudinal radioulnar dissociation (LRUD), usually in its chronic setting, after Essex-Lopresti injuries of the forearm.There are no sufficient clinical data to support reconstruction of the central band of the interosseous membrane in acute LRUD injuries.Clinical and cadaveric studies comparing autografts (palmaris longus, flexor carpi radialis and bone-patellar-bone), allografts (Achilles tendon) and synthetic ligaments have not shown superiority of one technique another; however, they have shown special concerns with respect to the use of synthetic grafts.Latrogenic fracture, decrease of rotational range of movement, iatrogenic nerve injury (superficial radial and median nerve), donor site morbidity with autografts and recurrent instability are the complications reported in literature after interosseous membrane reconstruction. Cite this article: 2019;4:143-150. DOI: 10.1302/2058-5241.4.180072.